2021
DOI: 10.2217/fon-2021-0585
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Surgery During the COVID-2019 Pandemic: Perioperative Management and Oncological and Anatomical Considerations

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has changed many aspects of our everyday lives and medical practice, including oncology treatment; thyroid cancer surgery is not an exception. The reported number of fine-needle aspirations performed during the first semester of 2020 was significantly reduced. Poorly differentiated, medullary and anaplastic thyroid tumors are considered important indications for immediate surgical intervention. By contrast, most well-differentiated carcinomas present slow growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We found that thyroid cancer cases during th epandemic period were seemed to decrease. The reason for this decrease may result from a decrease in the number of fine needle aspirations used in the diagnosis of thyroid cancers and in out patient treatments decreased in many parts of the world during the pandemic period 23 . It may be related to the number of fine needle aspiration, which is a highly effective diagnostic tool in the cytological diagnosis of the thyroid cancers and use of which was decreased in Sivas during the pandemic period and this finding was found to be consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…We found that thyroid cancer cases during th epandemic period were seemed to decrease. The reason for this decrease may result from a decrease in the number of fine needle aspirations used in the diagnosis of thyroid cancers and in out patient treatments decreased in many parts of the world during the pandemic period 23 . It may be related to the number of fine needle aspiration, which is a highly effective diagnostic tool in the cytological diagnosis of the thyroid cancers and use of which was decreased in Sivas during the pandemic period and this finding was found to be consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, there is a need to re-assess the protocols for surveillance and diagnosis of thyroid cancer. The procedures for diagnosis of thyroid nodules can be safely postponed ( 31 ); a few months of diagnostic delay during the COVID-19 pandemic has not negatively impacted most thyroid cancer patients or led to worse disease outcomes ( 32 ). However, patients with suspected MTC, ATC, or metastatic thyroid cancer (or a history of one or more of these diseases) should not delay fine-needle aspiration ( 31 ).…”
Section: Strategies For Surveillance and Diagnosis During The Covid-1...mentioning
confidence: 99%
“…The procedures for diagnosis of thyroid nodules can be safely postponed ( 31 ); a few months of diagnostic delay during the COVID-19 pandemic has not negatively impacted most thyroid cancer patients or led to worse disease outcomes ( 32 ). However, patients with suspected MTC, ATC, or metastatic thyroid cancer (or a history of one or more of these diseases) should not delay fine-needle aspiration ( 31 ). There is an important infectious disease risk associated with fine-needle aspiration: the collection and fixation steps may generate aerosols and droplets that spread viral particles.…”
Section: Strategies For Surveillance and Diagnosis During The Covid-1...mentioning
confidence: 99%
“…In this context, surgical activity for thyroid disease was also reduced [ 12 ]. During lockdowns, prioritization systems were applied [ 13 ] and thyroidectomy was still performed for clinically-significant thyroid malignancies and uncontrolled hyperthyroidism [ 14 ].…”
Section: Reduction and Postponement Of Thyroid Surgeriesmentioning
confidence: 99%